Conventional MPAs are not as effective as community co-managed areas in conserving top-down control in the Gulf of California. (December 2018) - Ulate, Karol; Alcoverro, Teresa; Arthur, Rohan; Aburto-Oropeza, Octavio; Sánchez, Carlos; Huato-Soberanis, Leonardo
Abstract: While undeniably successful in protecting nearshore marine ecosystems from overfishing, conventional marine reserves often impinge on the livelihoods of dependent coastal communities. Community co-managed areas may guarantee considerably more equity, but it is unclear if they can be as effective as conventional reserves in conserving critical trophic functions. We evaluated the effectiveness of different management regimes in the Gulf of California on fish biomass and echinoderm assemblages as proxies of key ecosystem processes on rocky shores. We compared multiple sites in a mixed (multi-use areas with regulated extraction) and core (no-extraction) federally-managed areas, a military MPA (where strict patrolling ensures no extraction), a co-managed reserve where government and communities are equally responsible, and unrestricted-access areas (non MPA). Fish biomass was higher in the military reserve and the community co-managed area reserve; echinoderm numbers were very low at these locations suggesting that they were strongly controlled by top-down processes. In contrast, federally-controlled reserves were virtually no different from unrestricted-access areas in numbers or composition of fish and echinoderms. Although federal managed reserves are the most common management regime across the Gulf, our data shows that they are highly ineffective in protecting ecosystem function. The relative effectiveness of co-managed reserves in this region suggests that fishers are more willing to comply when they have a stake in decision-making. Coastal conservation can benefit greatly by drawing from a wider suite of management options that engage local communities as key participants in the managing marine diversity and critical ecosystem functions. Highlights: We compared the effectiveness of five management regimes in the Gulf of California. Predatory fish numbers were highest in military and co-managed areas. These areas had the lowest echinoderm numbers, suggesting effective top-down control. Federal managed reserves did not differ from open areas in fish and echinoderms. Co-management is an equitable and effective alternative for managing rocky shores.